2018
DOI: 10.11604/pamj.2018.31.235.17709
|View full text |Cite
|
Sign up to set email alerts
|

Apport du Holter ECG dans le bilan étiologique des infarctus cérébraux à Brazzaville, Congo

Abstract: Déterminer la prévalence des troubles rythmiques au cours des infarctus cérébraux et identifier les facteurs prédictifs de la fibrillation atriale (FA) paroxystique. Il s'est agi d'une étude transversale, descriptive et analytique, menée à Brazzaville entre janvier 2012 et décembre 2016. Elle a porté sur une série consécutive de 267 patients victimes d'un accident vasculaire cérébral ischémique transitoire (n = 17) ou constitué (n = 250), documenté par un scanner cérébral. Tous ces patients ont bénéficié d'un … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
1
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 24 publications
1
1
0
1
Order By: Relevance
“…The nondipper rate was found to be 67%. Although this rate was very high, it was similar to previous data in the literature [ 20 - 22 ]. In the most recent comprehensive study, the prevalence of NDHT was found to be 70% in patients with HT under treatment and 75% in patients who were not under treatment [ 11 ].…”
Section: Discussionsupporting
confidence: 91%
“…The nondipper rate was found to be 67%. Although this rate was very high, it was similar to previous data in the literature [ 20 - 22 ]. In the most recent comprehensive study, the prevalence of NDHT was found to be 70% in patients with HT under treatment and 75% in patients who were not under treatment [ 11 ].…”
Section: Discussionsupporting
confidence: 91%
“…In the literature, the frequency of atrial fibrillation during cerebral infarctions is [17]. This great variability is probably due to methodological differences, not only related to the duration of the study and the size of the sample which is the case in our study, but also and especially to the methods used to detect AF.…”
Section: Discussionmentioning
confidence: 72%
“…Pour l'âge, une étude réalisée au Congo Brazzaville a eu le même résultat (Ikama et al, 2018). Plusieurs auteurs s'accordent à dire que les infarctus cérébraux relatifs à la FA surviendraient plus tardivement que les infarctus cérébraux d'autres mécanismes soit à un âge de 76,6 ans contre 68.4 ans dans l'étude d 'Hannon et al (2010).…”
Section: Discussionunclassified